SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN GURU TELADAN PADA SEKOLAH DASAR MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Setiyadi, Didik; Rofiah, Syahbaniar (Infotech: Journal of Technology Information, 2022)
The word learning is not foreign to some people, maybe you have heard it thousands of times, maybe the word brings a feeling of joy to yourself or boredom. Learning is currently carried out in various ways, namely online and face to face in the classroom. In the teaching and learning process, two directions are needed between teachers and students so that the messages and information conveyed can be absorbed properly. Teachers are at the forefront in determining the quality of school graduates, so it is necessary to select exemplary teachers. In order to improve the quality of educators and education personnel, as well as to give appreciation to the teaching profession, activities aimed at motivating teachers to improve their competencies are held, one of which is a competition for selecting exemplary teachers. In this study using the Simple Additive Weighting (SAW) method with the first step determining the value of the normalized rij performance rating and the second determining the preference for each alternative Vi. of the 4 candidates for Teacher A, Teacher B, Teacher C and Teacher D who were selected to be exemplary teachers with a score of 0.825, namely Teacher D.